Mortality after radial-only balloon aortic valvuloplasty: a long-term follow-up and a bridge-to-TAVI analysis - Achim Alexandru; Van den Eynde Jef; Szűcsborus Tamás; Sasi Viktor; Nagy Ferenc; Jambrik Zoltán; Nemes Attila; Varga Albert; Ruzsa Zoltán (Sciendo, 2023)
The benefits of distal radial balloon aortic valvuloplasty were recently reported: same efficacy as the classical femoral approach, with no vascular complications. The long-term outcomes for these patients remain unknown.